The Development of Islamic Big Book Learning Media For Early Children's Languages - Juli Maini Sitepu; Mawaddah Nasution; Widya Masitah (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
This article aims to develop Big Bookis learning media (Big Book Islami). The problems that occur are the children's language skills are still not optimal and the learning media used by the teacher is less attractive so that they are less able to improve children's language skills. This article uses a research and development approach. The data collection technique used in this research is a questionnaire and documentation method. Media that have been assessed by material experts and teachers are then given to students of Kindergarten ABA 13 Helvetia Medan as respondents and their language development is assessed by the teacher. The method used to analyze the data is expressed in the distribution of scores on a scale of five against a predetermined rating scale category. The results of Islamic Big Book Learning Media Development are declared suitable for use after being tested by developers, material experts, media experts, and users. Details of the data obtained from the test results include: material expert testing obtained a score of 4 and a presentation value of 80% with a decent category, media expert testing obtained a score of 4, and a presentation value of 80% with a decent category, and the results of children's language development through Islamic Big Book 80 media. .83 with a well-developed category. The results of the study show that Big Bookis media can improve children's language skills in Kindergarten ABA 13 Helvetia Medan.